O‘QUVCHILARDA O‘QISH SAVODXONLIGINI RIVOJLANTIRISH VA BAHOLASHGA DOIR PISA TOPSHIRIQLARI - Murodova, Sh. (SCIENCE and SOCIETY, 2021)
The article deals with the development and use of special educational tasks used in the lessons of the native language and literature, the system of tasks that reflect the content of the text, as well as assess the degree of their formation.
Keywords: poetic text; literacy; reading literacy; speaking skill; reading; understanding; creative thinking; logical thinking